Surfactant‐supplemented mixed bacterial cultures to produce hydrogen from paperboard mill wastewater. Issue 5 (2nd April 2015) - Farghaly, Ahmed; Tawfik, Ahmed; Eldin Ibrahim, Mona Gamal
<x xml:space="preserve">Abstract</x> Paperboard mill wastewater (PMW) mainly comprises complex compounds such as polysaccharides and lignin that are recalcitrant to microbial and enzymatic action. Surfactants supplementation was found to improve the enzymatic hydrolysis and reduce lignin content during anaerobic digestion process. However, much less attention has been given for the effectiveness of surfactants addition on hydrogen production from PMW under hyperthermophilic conditions. In this study, the mixed bacterial culture was supplemented with surfactants, namely PEG 6000 and Tween 80 (T80), to enhance the biodegradation process and hydrogen yield (HY). The results showed that increasing the concentration of T80 from 0.25 to 1.75% v/v significantly (p < 0.001) increased HY from 1.7 ± 0.02 to 2.6 ± 0.01 mmol/gCODinitial (where COD is chemical oxygen demand), respectively. However, with further increase in the concentration of T80 up to 2.5%, the HY dropped to 2 ± 0.04 mmol/gCODinitial. This was mainly due to a higher propionate (HPr) production. Similar trends were observed for PEG, where the maximum HY of 2.8 ± 0.02 mmol/gCODinitial was achieved at a concentration of 0.75 mg/L, which deteriorated at higher and lower concentrations of PEG. Fermentative hydrogen of 700 m3/day of PMW could support about 16.4% of total primary energy consumption of the factory.